2015
DOI: 10.20450/mjcce.2015.644
|View full text |Cite
|
Sign up to set email alerts
|

Effects of structural variations on the hydrogen bond pairing between adenine derivatives and thymine

Abstract: The hydrogen bonding between substituted adenines and thymine was investigated by density functional theory computations at the B3LYP/6-311+G(2d,2p) level. The effect of 20 different polar substituents at position 8 in adenine was examined in detail. Three different theoretical parameters, reflecting the electrostatics at the atoms involved in hydrogen bonding, were applied. An excellent correlation between electrostatic potentials at the bonding atoms in the monomer adenines and interaction energies was deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…14 It was found that the stability of tautomers of substituted adenine molecules strongly depends on solvation. It was also found 15 that, for 20 different substituents in the position 8 of adenine, electrostatic potentials at the bonding atoms of monomers correlate nicely with interaction energies of adenine-thymine pairs.…”
Section: Introductionmentioning
confidence: 85%
“…14 It was found that the stability of tautomers of substituted adenine molecules strongly depends on solvation. It was also found 15 that, for 20 different substituents in the position 8 of adenine, electrostatic potentials at the bonding atoms of monomers correlate nicely with interaction energies of adenine-thymine pairs.…”
Section: Introductionmentioning
confidence: 85%
“…They may lead to substantial changes in its electronic structure and, in consequence, to changes in its chemical/physicochemical/biochemical properties. , Therefore, knowledge of changes in the electronic structure of adenine caused by both the solvent and well-defined factors (e.g., introduction of substituents) exhibiting specific electron donating/accepting properties is of fundamental importance. It should be emphasized that their influence on hydrogen bonds was most often studied in structurally modified Watson-Crick base pairs, whereas their influence on properties of nucleic acid bases is much less represented in the literature. , …”
Section: Introductionmentioning
confidence: 99%
“…The relative stability of different conformations of adenosine was investigated due to the protonation at a low ab initio level . Recently, density functional theoretical calculations were used to explore the stability of different tautomers and hydrogen bonding pairs of DNA bases, but these studies mainly focused on analyses of the substituent effect on geometries, energies, charge distributions and hydrogen bonding interactions. ,, Until now, there have only been a few studies on theoretical analysis of vibrational spectra of these halogen-substituted adenine derivatives. , The assignment of observed Raman bands still limited to the optimized structures at the SCF/STO-3G level and the assignment of adenine analogues. , …”
Section: Introductionmentioning
confidence: 99%